Sero-prevalence of malaria and the knowledge, attitudes and practices relating to the prevention of malaria among indigenous people living in the central forest spine in peninsular Malaysia: a mixed-methods study - Kader Maideen, Siti Fatimah; Abdul Rashid; Ahmad, Nur Indah; Zahari, Siti Nur Afiqah; Awang Hamat, Rukman (BMC, 2022)
Background : Malaria is still a major public health threat in some parts of the world. Many countries are targeting to achieve malaria free status country. This study aimed to determine the sero-prevalence of malaria and the knowledge, attitudes and practices relating to the prevention of malaria among the indigenous adults living in the central forest spine in Peninsular Malaysia. Methods: A mixed method study was conducted in indigenous settlements in 2020. Blood film for malaria parasite (BFMP) was used to diagnose malaria in this study. A structured questionnaire was used to collect data from the participants. For the qualitative data, in-depth interviews were conducted and data was collected until data saturation was reached. Multiple linear regression was used to determine the predictors after adjusting for confounders. A p-value of < 0.05 is considered as statistically significant. Meaningful statements from the in-depth interviews were assigned to the relevant codes using NVivo version 12 software. Results: A total of 284 indigenous people participated in the study. The prevalence of malaria in this study was 0%. Those in the middle age group between 25 and 41 years and tested positive for malaria previously were significantly more likely to have better knowledge and attitude scores. Significant correlations were also observed between knowledge-attitude and knowledge-practice. For the qualitative results, most of the respondents were unsure of monkey malaria, but all were aware of human malaria. Conclusion: The present study highlighted the absence of malaria in the study population and relatively good knowledge, attitudes and practices relating to the prevention of malaria.